1974
DOI: 10.1037/h0036977
|View full text |Cite
|
Sign up to set email alerts
|

Short-term versus long-term effects of adrenal hormones on behaviors.

Abstract: Hypothesizes that short-term exposures to stress facilitate performances of serially repetitive, overlearned tasks and impair performances of perceptual restructuring tasks, while long-term exposures to stress produce the opposite behavioral effects. These effects are attributed, in part, to the length of exposure of the central nervous system to stress-elicited adrenal hormones (epinephrine and cortisol). Short-term exposures are believed to induce states of central adrenergic dominance that favor performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 142 publications
(142 reference statements)
1
8
0
Order By: Relevance
“…In a recent paper, Broverman, Klaiber, Vogel, and Kobayashi (1974) have for-warded an argument that in many ways is similar to that presented here. These investigators suggested that in short-term stress situations, release of epinephrine may stimulate central norepinephrine via the reticular activating system and the hypothalamus (see also Gellhorn, 1957), consequently resulting in increased responsivity.…”
Section: Effects Of Stress On Neurotransmitter Activitysupporting
confidence: 61%
See 1 more Smart Citation
“…In a recent paper, Broverman, Klaiber, Vogel, and Kobayashi (1974) have for-warded an argument that in many ways is similar to that presented here. These investigators suggested that in short-term stress situations, release of epinephrine may stimulate central norepinephrine via the reticular activating system and the hypothalamus (see also Gellhorn, 1957), consequently resulting in increased responsivity.…”
Section: Effects Of Stress On Neurotransmitter Activitysupporting
confidence: 61%
“…Accordingly, the net result may be one of greater imbalance of the catecholamine-cholinergic systems in favor of cholinergic action. Moreover, if decreased catecholamine-receptor stimulation occurs because of accumulated false transmitters, as suggested by Broverman et al (1974), a mechanism for increased ACh levels can be postulated, since dopamine apparently has a tonic inhibitory effect on ACh levels (Bartholini et al, 1973).…”
Section: Effects Of Stress On Neurotransmitter Activitymentioning
confidence: 99%
“…(Levine [ 19691 has assumed that variations in neonatal corticosterone permanently bias the animal's subsequent response to emotion-provoking stimuli.) Corticosterone also inhibits testosterone production-at least in adult males (Broverman, Klaiber, Vogel, & Kobayashi, 1974)-and, thus, the complementary changes in sexual behavior and open-field activity observed might be mediated by similar hormonal changes induced by early stress.…”
Section: Discussionmentioning
confidence: 99%
“…There is recent evidence that sex hormones can affect MAO activity and regulate adrenergic arousal (Broverman et al, 1974). In humans there are changing levels of MAO in association with blood oestrogen concentrations (Briggs & Briggs, 1972), the menstrual cycle (Klaiber et al, 1971), and in amenorrhoeic and menopausal women (Klaiber et al, 1971).…”
Section: Introductionmentioning
confidence: 99%